A Tychonoff non-normal space - V. Tzannes (International Journal of Mathematics and Mathematical Sciences)
A Tychonoff non-normal space is constructed which can be used for the construction of a regular space on which every weakly continuous (hence every θ-continuous or η-continuous) map into a given space is constant.